What are the potential advantages and disadvantages of merging health insurance funds? A qualitative policy analysis from Iran - Mohammad Bazyar; Vahid Yazdi-Feyzabadi; Nouroddin Rahimi; Arash Rashidian (BMC, 2020)
Abstract Background In countries with health insurance systems, the number and size of insurance funds along with the amount of risk distribution among them are a major concern. One possible solution to overcome problems resulting from fragmentation is to combine risk pools to create a single pool. This study aimed to investigate the potential advantages and disadvantages of merging health insurance funds in Iran. Methods In this qualitative study, a purposeful sampling with maximum variation was used to obtain representativeness and rich data. To this end, sixty-seven face-to-face interviews were conducted. Moreover, a documentary review was used as a supplementary source of data collection. Content analysis using the 'framework method' was used to analyze the data. Four trustworthiness criteria, including credibility, transferability, dependability, and confirmability, were used to assure the quality of results. Results The potential consequences were grouped into seven categories, including stewardship, financing, population, benefit package, structure, operational procedures, and interaction with providers. According to the interviewees, controlling total health care expenditures; improving strategic purchasing; removing duplication in population coverage; centralizing the profile of providers in a single database; controlling the volume of provided health care services; making hospitals interact with single insurance with a single set of instructions for contracting, claiming review, and reimbursement; and reducing administrative costs were among the main benefits of merging health insurance funds. The interviewees enumerated the following drawbacks as well: the social security organization's unwillingness to collect insurance premiums from private workers actively as before; increased dissatisfaction among population groups enjoying a generous basic benefits package; risk of financial fraud and corruption due to gathering all premiums in a single bank; and risk of putting more financial pressure on providers in case of delay in reimbursement with a single-payer system. Conclusion Merging health insurance schemes in Iran is influenced by a wide range of potential merits and drawbacks. Thus, to facilitate the process and lessen opponents' objection, policy makers should act as brokers by taking into account contextual factors and adopting tailored policies to respectively maximize and minimize the potential benefits and drawbacks of consolidation in Iran.